2007
DOI: 10.1007/s00535-007-2119-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induces adipose differentiation-related protein expression and lipid accumulation in the liver through inhibition of fatty acid oxidation in mice

Abstract: LPS induces transient lipid accumulation and expression of ADRP in the liver through inhibition of fatty acid oxidation by downregulation of the PPARalpha-related transcriptional mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…As systemic LPS injection may not only affect monocyte programming, but also other tissues such as the liver and metabolic processes2930, we further examined whether the re-programmed monocytes, instead of other systemic effects of LPS, may be causally involved in the exacerbation of atherosclerosis. To address this issue, we performed adoptive transfer experiment with in vitro programmed monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…As systemic LPS injection may not only affect monocyte programming, but also other tissues such as the liver and metabolic processes2930, we further examined whether the re-programmed monocytes, instead of other systemic effects of LPS, may be causally involved in the exacerbation of atherosclerosis. To address this issue, we performed adoptive transfer experiment with in vitro programmed monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…TLR4-mediated signaling in macrophages was also shown to play an important role in atherosclerosis formation (26,39). A recent in vivo study demonstrated that a single injection of LPS induced transient ADRP expression and lipid accumulation in liver in a mouse model (33). It did not, however, define the molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TLR2 and TLR4 stimulated formation of lipid bodies in leukocytes (9,37). It was shown that LPS/TLR4 mediates lipid metabolism by influencing the expression of some lipid-associated genes, upregulates sterol regulatory element-binding protein-1 and adipose fatty acid-binding protein, and downregulates scavenger receptor type B1 and PPAR␣ (10,21,22,33). In addition, it was also demonstrated using apolipoprotein E or LDL receptor knockout mice that TLR signaling, at least via TLR4 and TLR2, plays a significant role in atherosclerogenesis (26,39).…”
Section: Most Types Of Cells Store Lipid Droplets In Their Cytoplasmmentioning
confidence: 99%
“…Although it has been shown that several pathological or pharmacological stimuli enhance ADRP expression, the precise molecular mechanism regulating the expression is not fully elucidated. In previous studies, we and others demonstrated that an inflammatory signal, such as PMA or LPS, stimulates ADRP expression in macrophages (14,23,62), hepatocytes (46), and keratinocytes (15). We identified the Ets/AP-1 composite element in the mouse ADRP promoter and proved that it mediates, in part, the action of PMA or LPS, which enhances ADRP expression in RAW264.7 cells (23,62).…”
Section: Discussionmentioning
confidence: 99%